The maximal drawdown of the Brownian meander - Hu, Yueyun; Shi, Zhan; Yor, Marc (Electronic communications in probability, 2015)
Motivated by evaluating the limiting distribution of randomly biased random walks on trees, we compute the exact value of a negative moment of the maximal drawdown of the standard Brownian meander.